Blended Learning Challenges and the Contribution of Self-Regulated Learning to Health Care Students’ Resilience: A Cross-Sectional Study - Muhammad Andre Sugiharto; Rustiana Tasya Ariningpraja; Retno Lestari (AL-ISHLAH: Jurnal Pendidikan, 2025)
Health science students face significant challenges in post-COVID-19 learning, including time management difficulties, technological adaptation, and academic pressure. Blended learning, now a standard model in health education, demands strong self-regulated learning (SRL) and resilience for academic success and well-being. This cross-sectional study investigated the relationship between SRL and academic resilience (ARS) among 302 undergraduate students from various health disciplines at Universitas Brawijaya. Data were collected using validated instruments: the Self-Regulation for Learning Questionnaire and the Academic Resilience Scale (ARS-30). Descriptive statistics and Pearson correlation analysis were used to analyze the data. Findings revealed that 68.5% of students exhibited high SRL, and 68.9% demonstrated high ARS. The correlation analysis showed a statistically significant moderate positive relationship between SRL and ARS (r = 0.477, p 0.001). Students with higher levels of self-regulation were more likely to demonstrate greater resilience in navigating academic challenges within the blended learning environment. The results underscore the critical role of SRL in fostering academic resilience among healthcare students. These findings suggest that targeted strategies to enhance SRL—such as goal setting, time management training, and reflective practices—can improve students’ ability to adapt and persist in blended learning contexts. Educational institutions should implement structured learning support and psychological resilience programs to support student success.